Towards a periodization of the peruvian poetry of the Twentieth Century - Landa, Luis (2019)
The present text summarizes four scopes of an investigation that became the doctoral thesis of 2018: «Take the time of the word: review of the periodization of Peruvian poetry of the twentieth century.» In this way, herealizes the emptiness in the study that focuses exclusively on the evolution of our poetry. As a result of this poor situation, the transmission of history that develops from school to higher education expresses a mixtureof concepts - such as movements, currents, times and generations - that do not graph the nature of the lyric. Therefore, this article shows the alternative of the thesis of betting on the concept «period» that reorganizesthe perception of Peruvian poetry during the twentieth century. With an outlook of four periods, the poetic manifestations that emerged since the last years of the 19th century are reordered, as well as those that have been showing in these first decades of the 21st century. Likewise, the automatic way of appreciating the organization of poets for decades is ruled out under the false character of an artificial generation.